THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN LAGOS STATE, NIGERIA - Adegbenga, Onabamiro A.; M., Hassan E. (Sokoto Educational Review, 2020)
This research work investigated the influence of emotional intelligence on secondary school students’ academic achievement. A stratified random sampling technique was adopted to select 200 SS1 students from five senior secondary schools in Lagos state. A 33-item ‘Emotional Intelligence Scale with a Chrombach alpha value of 0.87 was used, the students’ JSS3 final result was used to measure the students’ academic performance. Three hypotheses were tested. The Pearson Product Moment Correlation and T-test statistical procedures were used to analyse data. The result indicated that there was a significant relationship between emotional intelligence and students’ academic achievement, no significant difference in the emotional intelligence of males and females students and no significant difference in the mean achievement of male and female students. Based on the findings, the implications for counseling were highlighted and it was recommended among others that enabling environment should be provided to make teaching and learning more productive.